Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together Berbantuan Media Powtoon terhadap Hasil Belajar Pendidikan Pancasila pada Siswa Kelas XI MA Ad-Dinul Qayim Lombok Barat - Lu’luul Jannah; M. Ismail; Edy Kurniawansyah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning outcomes in Pancasila Education are influenced by the instructional models and media. Teacher-centered instruction often results in low student engagement, preventing learning outcomes from reaching their potential. This study aims to determine the effect of the Numbered Head Together (NHT) cooperative learning model, assisted by Powtoon media, on the Pancasila Education learning outcomes of grade XI students at MA Ad-Dinul Qayim, West Lombok. A quantitative approach was adopted, utilizing a quasi-experimental method with a Nonequivalent Control Group Design. The study sample consisted of 43 students, including 22 students in the experimental group and 21 students in the control group. Data were collected through observation and testing and subsequently analyzed using the Shapiro-Wilk, Mann-Whitney U test, Levene’s statistic, Independent Samples t-test, and N-Gain Score analysis. The results revealed that the experimental group’s mean post-test score (85.27) was higher than that of the control group (72.76). The N-Gain test results showed that the experimental group achieved a score of 0.7208 (72.08%), falling into the high category, whereas the control group achieved a score of 0.6283 (62.82%), falling into the medium category. Thus, the Powtoon-assisted NHT model has a significant effect on Pancasila Education learning outcomes.